Efficacy and Brain Imaging Correlates of an Immersive Motor Imagery BCI-Driven VR System for Upper Limb Motor Rehabilitation: A Clinical Case Report - Vourvopoulos, Athanasios; Jorge, Carolina; Abreu, Rodolfo; Figueiredo, Patrícia; Fernandes, Jean-Claude; Bermúdez i Badia, Sergi (Frontiers in Human Neuroscience, 2019)
To maximize brain plasticity after stroke, several rehabilitation strategies have been explored, including the use of intensive motor training, motor imagery, and action observation. Growing evidence of the positive impact of virtual reality (VR) techniques on recovery following stroke has been shown. However, most VR tools are designed to exploit active movement, and hence patients with low level of motor control cannot fully benefit from them. Consequently, the idea of directly training the central nervous system has been promoted by utilizing motor-imagery (MI) based brain-computer interfaces (BCIs). To date, detailed information on which VR strategies lead to successful functional recovery is still largely missing, and very little is known about how to optimally integrate BCI and VR paradigms for stroke rehabilitation. The purpose of this study was to examine the efficacy of a BCI-VR system using a MI paradigm for post-stroke upper limb rehabilitation on functional assessments, and related changes in MI ability and brain imaging. To achieve this, a 60 years old male chronic stroke patient was recruited. The patient underwent a 3-week intervention in a clinical environment, resulting in 10 BCI-VR training sessions. The patient was assessed before and after intervention, as well as on a one-month follow-up, in terms of clinical scales and brain imaging using functional MRI (fMRI). Consistent with prior research, we found important improvements in upper extremity scores (Fugl-Meyer) and identified increases in brain activation measured by fMRI that suggest neuroplastic changes in brain motor networks. This study expands on the current body of evidence as more data are needed on the effect of this type of interventions not only on functional improvement but also through brain imaging to study the effect of the intervention on plasticity.